Studi Kepuasan Konsumen Berbasis Importance Performance Analysis pada E-Commerce Shopee - Ni Nyoman Santi Irayani Putri; Ni Nyoman Triana Prima Dewi; I Wayan Dode Sudiartana; I Gusti Ayu Ketut Giantari (Forum Manajemen, 2023)
Shopee is a mobile application-based online buying and selling e-commerce that is developing in Indonesia as the first consumer-to-consumer (C2C) marketplace. This study aims to find out how much Shopee's service quality is to determine customer satisfaction. This study uses a quantitative descriptive research, by measuring the level of conformity between customer expectations and company performance. The population in this study are Shopee application users throughout Indonesia. The sample in this study were Shopee application users who had purchased a product at least once within three months. The sampling method used purposive sampling method. The number of respondents who filled out the survey was 86 respondents. Data analysis techniques use the Importance Performance Analysis (IPA) method in which this method shows the relationship between the level of importance and performance. The level of importance and performance is measured based on the average value given by each respondent on each indicator. The correlation of each item to the total score of each statement for the variables/attributes of Efficiency, Fulfillment, System Availability, Privacy, Responsiveness, Compensation, Contact. All of them produce rtables above 0.361 with a significance value of 0.060 (6%). Thus, the entire statement of research variable items is valid and reliable. This means that overall all the indicators that are considered important are in accordance with consumer expectations so that there is no need to prioritize a particular indicator.